PROTERRA IBERIAN-AMERICAN NETWORK: HISTORY, INVENTORY AND PERSPECTIVES - Penido de Rezende, Marco Antônio; Neves, Célia; Guerrero Baca, Luis Fernando (Memorias del Seminario Iberoamericano de Arquitectura y Construcción con Tierra - SIACOT, 2012)
The PROTERRA Iberian-American Network is a collaborative organization established in order to investigate, preserve and disseminate earthen architecture and its construction technology. It brings together over 100 professionals from 21 countries of the region in various research areas, such as teaching, design, construction, training and dissemination. The Network has published nine printed books, 20 CD-ROM and other electronic publications, and has promoted more than 60 courses and workshops, and over 30 conferences and seminars, among which 12 Iberian-American Seminars of Architecture and Earthen Construction (SIACOT) were accomplished under its direct auspices. Currently, the Network has a signiicant role in research and dissemination of earthen architecture and construction throughout the Iberian-American region, both from the point of view of conservation, as well as construction technology, and new architecture. The origins of this organization began in October 2001, as an Iberian-American research project, supported by CYTED (Ciencia y Tecnologia para el Desarrollo), which led to interesting and unusual contributions to the discipline, particularly those that resulted in the creation of the Network at the end of the Proterra project, in February 2006. Since then, without any formal funding, the Network continues developing various activities from the initiative of its members, and has even increased the number of courses and seminars in relation to previous years, when working within a funded rese arch project. The dynamism and interesting past of the Network led to the development of a study conducted in 2010 at the University of Oregon, USA. This paper presents part of the results of that study, which discusses the different activities accomplished by the Network, and incorporates also the oral history and actions of one of its members, as wel las the irst and the second Coordinators of the Network.